MATANA: A Reconfigurable Framework for Runtime Attack Detection Based on the Analysis of Microarchitectural Signals - Yuxiao Mao; Vincent Migliore; Vincent Nicomette (Applied Sciences, 2022)
Microarchitectural attacks exploit target hardware properties to break software isolation techniques used by the processor. These attacks are extremely powerful and hard to detect since the determination of the program execution’s impact on the microarchitecture is at the same time not precisely understood and not easily observable at the software layer. Some approaches have attempted to benefit from existing hardware to better understand and detect the microarchitectural attacks (i.e., Hardware Performance Counters or Arm CoreSight), but such hardware was not meant to be used for cybersecurity, with reduced choice on observable signals and limited throughput of information. In this paper, we propose MATANA, an open and adaptive reconfigurable hardware/software co-designed framework. Combining fine-grained analysis of microarchitectural signals and software support, MATANA allows to design and assess detection mechanisms for attacks by characterizing their microarchitectural effects—in particular, microarchitectural attacks, but also some high-level attacks such as return-oriented programming attacks. The paper also describes a prototype implementation, built with a RISC-V softcore processor Rocket running Linux 4.15 on a Virtex-6 FPGA. We successfully used MATANA to analyze cache side-channel attacks and build attack detection logic from two different perspectives: instruction-based and memory-access-based. We also successfully detected return-oriented programming attacks by exhibiting a specific behavioral pattern on the microarchitecture.